Pengaruh Corporate Social Responsibility, Biaya Lingkungan, Dan Ukuran Perusahaan Terhadap Kinerja Keuangan - Putri Adelia Siregar; Achmad Maqsudi (Transformasi: Journal of Economics and Business Management, 2024)
This study aims to analyze the effect of Corporate Social Responsibility (CSR) disclosure, Environmental Costs, and Company Size on the Financial Performance of mining sub-sector manufacturing companies listed on the Indonesia Stock Exchange. In this study using the type of quantitative data with the acquisition of secondary data derived from financial statements. Sampling using Purposive Sampling technique with 32 samples in this study. The method used in this study adopts the Partial Least Squares Structural Equation Modeling (PLS-SEM) method to analyze the relationship between CSR disclosure, Environmental Costs and Company Size. The results of this study indicate that Corporate Social Responsibility (CSR) has a positive but insignificant effect on financial performance. While Environmental Costs and Company Size have a negative and significant effect on Financial Performance.